Decentralizing Finance via Cryptocurrencies and Tokenization of Assets and Peer-to-Peer Platforms - Hazik Mohamed (The Postgraduate of Institut Agama Islam Negeri Metro Lampung, 2021)
The rationale behind this research is to demonstrate the tokenization effects of the blockchain on all types of assets, and how blockchain technology might improve the way we view digital exchange and use digital money. The finance industry is progressing towards innovative solutions, capable of dealing with traditional problems and of increasing efficiency, sustainability and accountability. This progression may also address market failures within the economy. In our conceptual chapter, we provide a short discussion of the decentralization of finance and where we are today. We begin with the fundamentals of money and the evolution of cryptocurrency issuance from ICOs to STOs then to stablecoins like CBDCs. We then examine the concept of tokenizing various types of assets and deliberate on a conceptualization of a tokenized capital markets trading platform. To clarify tokenization and its benefits, we provide an example on the tokenization concept for agriculture and livestock in raising capital for small farms. Finally, we conclude discussions on concerns for privacy and security which emphasizes on self-governance, self-regulation and cybersecurity measures.